Culturally responsive counseling with Latinas/os - Arredondo, Patricia; Gallardo-Cooper, Maritza; Delgado-Romero, Edward A.; Zapata, Angela L. (Alexandria, VA : American Counseling Association, 2014)
This book provides culture-centered assessment and intervention strategies for effective clinical practice with Latina/o individuals and families. Mental health professionals will gain new and expanded cultural competence as they learn to sensitively and ethically integrate Latino values into their work. Throughout the text, case scenarios illustrate ways to work successfully with clients of all ages. A sample culture-centered clinical interview is included, along with a listing of Latino-specific mental health resources. Topics discussed include roles, relationships, and expectations in Latino families; cultural and bicultural values; gender role socialization; generational differences; identity and acculturation issues; educational values and achievement; Latinas/os in the workforce; and religious beliefs and practices.
Who Are Latinos / Patricia Arredondo, Maritza Gallardo-Cooper, Edward A Delgado-Romero, Angela L Zapata -- Latino Worldviews and Cultural Values / Patricia Arredondo, Maritza Gallardo-Cooper, Edward A Delgado-Romero, Angela L Zapata -- Acculturation and Enculturation Processes / Patricia Arredondo, Maritza Gallardo-Cooper, Edward A Delgado-Romero, Angela L Zapata -- The Complexity of Latina/o Multidimensional Identity / Patricia Arredondo, Maritza Gallardo-Cooper, Edward A Delgado-Romero, Angela L Zapata -- Education / Patricia Arredondo, Maritza Gallardo-Cooper, Edward A Delgado-Romero, Angela L Zapata -- Employment, Economics, and the Psychology of Working / Patricia Arredondo, Maritza Gallardo-Cooper, Edward A Delgado-Romero, Angela L Zapata -- Situational Stressors and Their Effects / Patricia Arredondo, Maritza Gallardo-Cooper, Edward A Delgado-Romero, Angela L Zapata -- La Familia Latina: Strengths and Transformations / Patricia Arredondo, Maritza Gallardo-Cooper, Edward A Delgado-Romero, Angela L Zapata -- Planning for Culture-Centered Assessment and Practice / Patricia Arredondo, Maritza Gallardo-Cooper, Edward A Delgado-Romero, Angela L Zapata -- Latinas/os in Counseling / Patricia Arredondo, Maritza Gallardo-Cooper, Edward A Delgado-Romero, Angela L Zapata -- Ethics and Organizational Cultural Competencies / Patricia Arredondo, Maritza Gallardo-Cooper, Edward A Delgado-Romero, Angela L Zapata -- The Future of Latina/o-Centered Counseling / Patricia Arredondo, Maritza Gallardo-Cooper, Edward A Delgado-Romero, Angela L Zapata -- Appendix A: Culture-Centered Clinical Interview-Revised -- Appendix B: Latino sMental Health Resources.
Includes bibliographical references (pages 229-268) and index.
Print version record.
Keywords: Hispanic Americans -- Counseling of; Hispanic Americans -- Social conditions; Hispanic Americans -- Economic conditions; Hispanic Americans -- Population; PSYCHOLOGY -- Applied Psychology; SELF-HELP -- Personal Growth -- General; SELF-HELP -- Personal Growth -- Happiness; SELF-HELP -- Personal Growth -- Success; Hispanic Americans -- Counseling of; Hispanic Americans -- Economic conditions; Hispanic Americans -- Population; Hispanic Americans -- Social conditions; Electronic books